The Pedagogical Conditions of Usage of Achievements of Ecological Education of Last Years of the XX Century under Modern Conditions - Kravets’, Nadiya (Pedagogical Discourse, 2012)
The pedagogues’ achievements in ecological education of children of 6-7 years of age under modern conditions of last years of the XX century are analyzed in the article.